A Tetraperylene Diimides Based 3D Nonfullerene Acceptor for Efficient Organic Photovoltaics. Issue 4 (27th February 2015) - Liu, Shi‐Yong; Wu, Chen‐Hao; Li, Chang‐Zhi; Liu, Sheng‐Qiang; Wei, Kung‐Hwa; Chen, Hong‐Zheng; Jen, Alex K.‐Y.
Abstract : A nonfullerene acceptor based on a 3D tetraperylene diimide is developed for bulk heterojunction organic photovoltaics. The disruption of perylene diimide planarity with a 3D framework suppresses the self‐aggregation of perylene diimide and inhibits excimer formation. From planar monoperylene diimide to 3D tetraperylene diimide, a significant improvement of power conversion efficiency from 0.63% to 3.54% can be achieved.